Hubungan dukungan keluarga dengan self management pada pasien diabetes melitus - Ramadani, Yulita; Hermawan, Nur Sefa Arief; Arisandi, William (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Way Halim II Community Health Center (Puskesmas) experienced a surge in Diabetes Mellitus (DM) cases, from 20 patients (1.88%) in 2020 to 473 patients (33.8%) in 2024. This surge highlights the importance of optimal self-management in patients with diabetes mellitus. Purpose: To determine the relationship between family support and self-management in DM patients. Method: This quantitative study used a cross-sectional approach, with a sample of 105 out of 141 patients selected using the Slovin formula and purposive sampling technique. Data were collected through interviews using a questionnaire and analyzed using the Chi-Square test. Results: Univariate analysis revealed 50 respondents (47.6%) with good family support and 57 respondents (54.3%) with good self-management. The Chi-Square test showed a significant relationship between family support and self-management (p-value = 0.000).Conclusion: There is a relationship between family support and self-management in patients with diabetes mellitus.   Keywords: Diabetes Mellitus; Family Support; Self-Management.   Pendahuluan: Puskesmas Way Halim II mengalami lonjakan kasus Diabetes Mellitus (DM) dari 20 pasien 1.88% tahun 2020 dan menjadi 473 pasien 33.8% pada tahun 2024. Lonjakan ini menyoroti pentingnya pengelolaan mandiri (self-management) yang optimal pada pasien dengan diabetes mellitus. Tujuan: Untuk mengetahui hubungan antara dukungan keluarga dengan self-management pada pasien DM. Metode: Penelitian kuantitatif dengan pendekatan cross-sectional dengan sampel sebanyak 105 orang dari 141 pasien yang dipilih menggunakan rumus Slovin dan teknik purposive sampling. Data dikumpulkan melalui wawancara menggunakan kuesioner dan dianalisis dengan uji Chi-Square. Hasil: Uji analisis univariat diperoleh sebanyak 50 responden (47.6%) dengan dukungan keluarga yang baik dan 57 responden (54.3%) dengan self-management yang baik. Uji Chi-Square menunjukkan hubungan signifikan antara dukungan keluarga dan self-management (p-value = 0.000). Simpulan: Ada hubungan antara dukungan keluarga dengan self management pada pasien diabetes melitus.   Kata Kunci: Diabetes Mellitus; Dukungan Keluarga; Self-Management.